2020
DOI: 10.1145/3386040
|View full text |Cite
|
Sign up to set email alerts
|

Browser Fingerprinting

Abstract: With this paper, we survey the research performed in the domain of browser fingerprinting, while providing an accessible entry point to newcomers in the field. We explain how this technique works and where it stems from. We analyze the related work in detail to understand the composition of modern fingerprints and see how this technique is currently used online. We systematize existing defense solutions into different categories and detail the current challenges yet to overcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
79
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 42 publications
0
79
0
1
Order By: Relevance
“…Only in the next study [10], where the research was conducted on a larger number of users, was it shown that fingerprinting can become a unique identifier. Works on browser or device fingerprinting usually contain comprehensive information on specific features comprising the fingerprint [3,10,11,12,14]. The studies also focus on the analysis of stability of particular parameters [3,12], examining different types of browsers [11,12] or applied security features limiting the possibility of obtaining fingerprint features [12].…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Only in the next study [10], where the research was conducted on a larger number of users, was it shown that fingerprinting can become a unique identifier. Works on browser or device fingerprinting usually contain comprehensive information on specific features comprising the fingerprint [3,10,11,12,14]. The studies also focus on the analysis of stability of particular parameters [3,12], examining different types of browsers [11,12] or applied security features limiting the possibility of obtaining fingerprint features [12].…”
Section: Related Workmentioning
confidence: 99%
“…A browser or device fingerprint is a set of data related to the user device. It contains information about the hardware, operating system and browser, and its configuration [11]. The information is collected only directly from the browser of a user by Javascript and by a web server.…”
Section: Definitionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, our scenario can handle situations where, two browser extensions developed by the same person or company but placed for instance at the beginning and at the end of the execution queue will actually access to different information and thus, collaborate to perform attacks like browser hijacking [19,13], or fingerprinting [15,10] attacks.…”
Section: Attacker Modelmentioning
confidence: 99%
“…Device fingerprinting is very popular in internet-connected general purpose computing devices to track user behaviour and application usage. Some of the interesting applications include browser fingerprinting for web analytics, user tracking, fraud detection and accountability [9,23,27] and have gained a significant interests from cyber-security community. While it is clear that device fingerprinting can bring a lot of benefits -especially for providing automated and customisable user experience -there are also concerns that it can pose security and privacy risks [29,39].…”
Section: Introductionmentioning
confidence: 99%